PROGRAM REGENERASI TERHADAP DEGRADASI BUDAYA CINA BENTENG DI KOTA TANGERANG - Ronaldo, Ronaldo; Jayanti, Theresia Budi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
Cina Benteng are ethnic Chinese who dominate the Tangerang area. Regeneration activities in improving the quality of cultural elements to deal with the problem of cultural degradation have become the focal point for architectural program development. The problem of cultural degradation from modernization factors increasingly makes the value of a culture less visible and diminished by developments over time. The regeneration program is a development that maintains cultural heritage, traditions, and activities passed down from generation to generation, becoming a combination of programs in one complete space. Program conditions that have been supported by the surrounding social context which has been well acculturated support the program. With the regeneration program, it is hoped that it can become an important reference as a form of returning the memories that form the active interaction patterns of Cina Benteng, in order to maintain traditions passed down from generation to generation. The method of this research uses qualitative methods, through direct observation of existing buildings that have become icons for preserving the Cina Benteng cultural heritage. Analysis from Cina Benteng people in maintaining traditions becomes a reference for selected "regeneration" programs and activities, namely popular, potential, and ritual programs with spatial elements. The results of this research develop the adaptation of the activities of Cina Benteng community into a proposed regeneration program that is felt by users, the "Bakti" program which can be used as a design development, while also fighting cultural degradation. Keywords: activities; cultural; cina benteng; degradation; regeneration Abstrak Cina Benteng merupakan etnis Tionghoa yang mendominasi kawasan Tangerang. Aktivitas regenerasi dalam meningkatkan kualitas elemen budaya untuk menghadapi masalah degradasi budaya, menjadi titik fokus pengembangan program secara arsitektur. Masalah Degradasi budaya dari faktor modernisasi, semakin membuat nilai suatu kebudayaan semakin kurang terlihat dan tergilis oleh perkembangan zaman. Program regenerasi menjadi pengembangan yang menjaga warisan budaya, tradisi, serta aktivitas turun-temurun, menjadi gabungan program dalam suatu ruang yang utuh. Kondisi program yang sudah didukung dari konteks sosial sekitar yang sudah terakulturasi dengan baik, mendukung program. Dengan adanya program regenerasi, diharapkan dapat menjadi acuan penting sebagai bentuk pengembalian memori-memori yang membentuk pola interaksi aktif user Cina Benteng, dalam menjaga tradisi turun-menurun. Metode dari penelitian ini menggunakan metode kualitatif, melalui pengamatan langsung ke eksisting bangunan yang sudah menjadi ikon menjaga warisan kebudayaan Cina Benteng. Analisis dari sudut pandang Cina Benteng dalam menjaga tradisi, menjadi acuan untuk program dan aktivitas “regenerasi” terpilih, yaitu program populer, potensial, dan ritual dengan elemen spasial. Hasil Penelitian ini mengembangkan adaptasi aktivitas masyarakat Cina Benteng menjadi usulan program regenerasi yang dirasakan oleh user, program “Bakti” yang dapat dijadikan pengembangan desain, sekaligus melawan degradasi budaya.